Sexual behaviour and knowledge of adolescent males in the Molopo region of Bophuthatswana - M. Kau (AOSIS, 1991)
Teenage pregnancy is one of the many public health problems facing the community in Bophuthatswana and neighbouring areas: Health professionals have attempted to address the problem yet little has been done to determine the role of the adolescent male in the prevention of this community problem. This study addresses the male adolescent's sexual behaviour, his attitude towards contraception, contraceptive use and premarital pregnancy. The study revealed that most of the respondents commenced sexual practices at about 12years of age. These young men believed that girls should prove their fertility before marriage, although they viewed contraception as a joint responsibility between the two partners. The respondents were found to have a positive attitude towards contraception and contraceptive use, yet when they were asked what method of contraception they used since they were sexually active, only 24,5% reported use of a condom. Ignorance about reproduction and the effects of contraceptives Was confirmed When 48% of the respondents indicated that they were unaware of the fact that pregnancy could result from first coitus, and they also believed that oral contraceptives had dangerous side effects. The study further revealed that parents did not discuss teenage pregnancy and contraception with their children, instead this subject was discussed among friends at school. Respondents expressed fear when asked why the subject was never discussed with parents, some actually stated that their parents would 'flog' them if they initiated the subject on sex and related matters. The urgent need for formalised sex education in Bophuthatswana was expressed by 77% of the respondents.